2007
DOI: 10.1007/s00415-006-0433-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-deep brain stimulation — gradual non-stimulation dependent decrease in strength with attenuation of multiple sclerosis tremor

Abstract: Tremor in multiple sclerosis is considered to be a persistent and progressive sign. We describe five patients with multiple sclerosis in whom upper limb tremor severity gradually decreased over a period of several years after deep brain stimulation. In every case this attenuation of tremor was accompanied by increasing pyramidal weakness in the relevant upper limb. In two patients this attenuation of tremor remained after stimulation was permanently switched off. In one other patient, where upper limb strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…This suggests that the presence of tremor accounts for part of the disability measured by the ONLS, similarly suggested by Ahlskog et al 26. Interestingly, in multiple sclerosis tremor, as limb weakness progresses, tremor may improve, suggesting a necessary role for limb strength in generating tremor 27. This may similarly be true for patients with inflammatory neuropathy and tremor but we observed that none of our patients reported worsening of tremor associated with improvement in their neuropathy (and strength) after treatment with intravenous immunoglobulins or other immunomodulators.…”
Section: Discussionsupporting
confidence: 58%
“…This suggests that the presence of tremor accounts for part of the disability measured by the ONLS, similarly suggested by Ahlskog et al 26. Interestingly, in multiple sclerosis tremor, as limb weakness progresses, tremor may improve, suggesting a necessary role for limb strength in generating tremor 27. This may similarly be true for patients with inflammatory neuropathy and tremor but we observed that none of our patients reported worsening of tremor associated with improvement in their neuropathy (and strength) after treatment with intravenous immunoglobulins or other immunomodulators.…”
Section: Discussionsupporting
confidence: 58%
“…High-frequency stimulation is required. Tremor occurring in multiple sclerosis can also respond [51], although these patients often have coexisting disabling ataxia which may be less predictably responsive to the surgery. The extent of functional disability due to tremor, rather than coexisting ataxia should be clarified during preoperative assessment.…”
Section: Vim Dbs For Non-pd Tremormentioning
confidence: 95%
“…102 This permanent tremor reduction has been attributed to limb weakness (occurring with MS progression) preventing the expression of tremor. 102 …”
Section: Treatmentmentioning
confidence: 99%